SOCIAL COMPETENCE AS A PREDICTOR FOR SUCCESSFUL SOCIAL INTEGRATION - Alina Gabriela ANGHEL; Mariana DOGARU (Association of Social and Educational Innovation, 2021)
Social competence is defined as "the characteristic of people capable of producing a desirable social influence on others" (Marcus S., 1999), a type of behaviour leading to social performance (Chelcea, 2013)", an empathic aptitude and the ability to develop social relationships. The following explanatory paradigm has been considered: the formation and development of social competences are conditioned by a series of intentional factors specific to each person (personality, capacity, social skills) and external factors specific to the external environment (group sentiment, group social processes).